Overload and its effects on sports injuries among senior football players - Amenellah, rachid; hbora, Mohammed; chahat, Mourad (sports creativity, 2025)
The issue of injury to the human body and its various systems resulting from excessive physical exertion is considered by scientists and sports specialists to be one of the most important issues of scientific research in the field of competitive sports training. This importance stems from the fact that physical exertion represents one of the main means of raising the level of physical and integrated athletic performance... Despite the great development in the field of competitive sports training and the sciences related to it during the last decade of the twentieth century, and despite the enormous leap achieved by applied research in this field, during which medical sciences contributed a large share to raising the level of athletes in general and football players in particular. However, many aspects require further research, experimentation, and investigation to uncover their mysteries and secrets, especially those related to the reactions and timing of the human body's systems when faced with excessive strain. Undoubtedly, there are many reasons for sports injuries, particularly among football players, often linked to training or competition conditions, especially those related to technique and tactics, as well as physical, health, and psychological factors. Sports injuries usually result from errors in training organization or from overloading the body's systems and failing to gradually increase the load correctly, which ultimately leads to various sports injuries among athletes. The nature of the relationship between overload and sports injuries is also a key consideration.